Developing entrepreneurial competencies focused on student learning through open educational digital resources - De Armas Cristancho, Diana Jeannette; Ojeda Enriquez, Miguel Antonio (Rastros Rostros, 2021)
Entrepreneurship, as an activity of designing, launching, and managing a new business, allows its authors’ per-sonal and professional growth, urging them to build new business fabrics. Therefore, it is required to develop entrepreneurial skills such as creativity, team and collaborative work, critical thinking, and problem-solving. For the above, the research consisted of implementing the student-centred learning strategy mediated by open educational digital resources to analyze whether it favours the development of entrepreneurial skills in ten-th-grade students. Eighteen students and two teachers participated in the study, a non-probabilistic sample by convenience, with a qualitative approach of descriptive scope and action research type conducted in four phases: 1. Detect and diagnose the problem; 2. Likewise, data were collected using: pilot test, semi-structu-red interviews, electronic questionnaires, and content analysis; categories, subcategories and a descriptive matrix of frequencies and percentages were used for data analysis. The results obtained allowed the study of strengths and weaknesses in developing entrepreneurial competencies through implementing the focused learning strategy. Where it was concluded that self-learning through digital resources are tools that empower and contribute to the development of entrepreneurial skills in students within the educational environment
Keywords: MICEA; digital educational resources; entrepreneurial competencies; student-centered learning